Efficiency and safety of HAIC combined with lenvatinib and tislelizumab for advanced hepatocellular carcinoma with high tumor burden: a multicenter propensity score matching analysis - Zhao, Zhonghua; Jiang, Xiongying; Wen, Shiping; Hao, Yanzhang (Frontiers in Pharmacology, 2025)
PurposeThe present work focused on assessing whether hepatic arterial infusion chemotherapy (HAIC) combined with lenvatinib and tislelizumab was safe and effective on advanced hepatocellular carcinoma (HCC) showing high tumor burden.MethodsIn the present multicenter retrospective study, treatment-naive advanced HCC patients (BCLC stage C) showing high tumor burden (maximum diameter of intrahepatic lesion beyond 7 cm) treated with lenvatinib and tislelizumab with or without HAIC were reviewed for eligibility from June 2020 to June 2023. Baseline differences between groups were mitigated by propensity score matching (PSM). Our primary endpoint was overall survival (OS); and secondary endpoints included adverse events (AEs), progression-free survival (PFS), disease control rate (DCR) and objective response rate (ORR) according to RECIST 1.1 criteria, respectively.ResultsAfter eligibility reviewed, total 162 patients treated with lenvatinib and tislelizumab were enrolled: 63 patients with HAIC (HTP group), and the remaining 99 patients without HAIC (TP group). After PSM 1:1, 47 cases were evenly divided into each group. Of them, HTP group showed significant prolonged median OS compared with TP group (16.6 versus 21.0 months; hazard ratio [HR]: 0.26, 95% confidence interval [CI]: 0.35–0.98; p = 0.039), and median PFS of HTP group was also prolonged (8.9 versus 11.6 months; HR: 0.55, 95% CI: 0.34–0.87; p = 0.010). Higher DCR and ORR could be observed in HTP relative to TP groups (ORR: 53.2% versus 17.0%, p < 0.001; DCR: 87.2% versus 61.7%, p = 0.004). The severe AEs (grade 3/4) and all grades were comparable between the groups, while all of these AEs could be controlled, and AEs of grade 5 were not reported.ConclusionHAIC combined with lenvatinib and tislelizumab is the candidate treatment for advanced HCC patients because of its improved prognosis and acceptable safety.